1993
DOI: 10.1507/endocrj.40.231
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Galanin-Immunoreactive Cells in the Anterior Pituitary of Male Monkeys (Macaca fascicularis).

Abstract: Abstract. The localization of galanin (GAL) was studied in the anterior pituitary of adult male macaque monkeys immunohistochemically.GAL-immunoreactive fiber bundles were noted in the posterior lobe of the pituitary. Cells immunoreactive for GAL were observed in the anterior lobe, and colocalization studies revealed that GAL-like immunoreactivity was present in gonadotrophs and thyrotrophs. The differences among the monkey, human and rat in GAL-immunoreactive localization may indicate that the regulation of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Studies on female rats with an altered galanin gene have confirmed that proliferation of lactotrophs under a high dose of oestrogen can be completely abolished (Wynick et al, 1998b), but galanin has also been associated with many other pituitary functions, such as the release of GH or LH, FSH and ACTH in humans. For further reading, we recommend the following references (Vrontakis et al, 1989(Vrontakis et al, , 1996Gabriel et al, 1989Gabriel et al, , 1990Calvo et al, 1990;Hooi et al, 1990aHooi et al, , 1997O'Halloran et al, 1991;Hyde and Howard, 1992;Niimi et al, 1993;Moore et al, 1994;Giustina et al, 1994;Hyde et al, 1996Hyde et al, , 1998Sauer-Ramirez et al, 1996;Hammond et al, 1997;Ceresini et al, 1997;Cai et al, 1998;Todd et al, 1998;Baranowska et al, 1999;Ren et al, 1999;Shen et al, 1999;Zdrojewicz and Sowinska, 2000;Elsaesser, 2001). This is in agreement with the presence of galanin in all pituitary cells during development; they all express galanin which, in the adult, may potentially activate specific functions in specific endocrine cells of the pituitary.…”
Section: Discussionsupporting
confidence: 65%
“…Studies on female rats with an altered galanin gene have confirmed that proliferation of lactotrophs under a high dose of oestrogen can be completely abolished (Wynick et al, 1998b), but galanin has also been associated with many other pituitary functions, such as the release of GH or LH, FSH and ACTH in humans. For further reading, we recommend the following references (Vrontakis et al, 1989(Vrontakis et al, , 1996Gabriel et al, 1989Gabriel et al, , 1990Calvo et al, 1990;Hooi et al, 1990aHooi et al, , 1997O'Halloran et al, 1991;Hyde and Howard, 1992;Niimi et al, 1993;Moore et al, 1994;Giustina et al, 1994;Hyde et al, 1996Hyde et al, , 1998Sauer-Ramirez et al, 1996;Hammond et al, 1997;Ceresini et al, 1997;Cai et al, 1998;Todd et al, 1998;Baranowska et al, 1999;Ren et al, 1999;Shen et al, 1999;Zdrojewicz and Sowinska, 2000;Elsaesser, 2001). This is in agreement with the presence of galanin in all pituitary cells during development; they all express galanin which, in the adult, may potentially activate specific functions in specific endocrine cells of the pituitary.…”
Section: Discussionsupporting
confidence: 65%
“…Abundant evidence indicates that galanin is expressed in the mammalian anterior pituitary as mRNA and protein (56)(57)(58)(59)(60)(61). In situ hybridization and ICC showed that galanin-positive cells are: i) in female rats predominantly lactotrophs (62)(63)(64)(65), where galanin is co-localized with prolactin in the secretory granules (66); ii) in male rats mainly somatotrophs, thyreotrophs (61) and corticotrophs (65,67); iii) in adult male monkeys thyreotrophs and gonadotrophs (68); and iv) in normal human pituitary and pituitary adenomas almost exclusively corticotrophs (69,70). Galanin-positive nerve fibers were found in the dog, monkey and human anterior pituitary (71,72).…”
Section: Expression Of Galanin and Its Receptors In The Hpa Axismentioning
confidence: 99%